A systematic review and meta‐analysis of locoregional treatments for in‐transit melanoma. Issue 7 (7th February 2019) - Read, Tavis; Lonne, Michael; Sparks, David S.; David, Michael; Wagels, Michael; Schaider, Helmut; Soyer, H. Peter; Smithers, B. Mark
Abstract: Background and Objectives: In‐transit melanoma (ITM) metastases present a therapeutic challenge and management decisions can be difficult. There are multiple treatments available, with differing efficacy, and supported by different levels of evidence. The primary objective was to perform a systematic review and where suitable, a meta‐analysis of the literature reporting on the use of locoregional treatments for the management of ITM. Methods: An independent review was conducted including a comprehensive search of the National Library of Medicine using PubMed, MEDLINE, Embase, and Cochrane Library databases. Key data were tabulated, synthesized and pooled to calculate relevant weighted effect sizes for each therapy using random‐effect models. The statistical heterogeneity was calculated using the Higgins' method. Results: Of the initial 32 612 articles identified, 57 original articles satisfied eligibility criteria. Eight treatment modalities were identified comprising: amputation (7); hyperthermic isolated limb perfusion (15); isolated limb infusion (8); carbon dioxide laser (9); PV‐10 intralesional therapy (5); IL‐2 intralesional therapy (8); imiquimod (7); diphenylcyclopropenone (3). Only amputation and topical imiquimod were suitable for formal meta‐analysis. Conclusions: All of the assessed therapies have significant selection bias. Variable levels of evidence support the ongoing use of locoregional treatments and these may significantly improve disease‐free survival.